2019
DOI: 10.3390/ijms20215442
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rice Large Grain Gene GW2 by Whole-Genome Sequencing of a Large Grain-Isogenic Line Integrated with Japonica Native Gene and Its Linkage Relationship with the Co-integrated Semidwarf Gene d60 on Chromosome 2

Abstract: Genetic analysis of “InochinoIchi,” an exceptionally large grain rice variety, was conducted through five continuous backcrosses with Koshihikari as a recurrent parent using the large grain F3 plant in Koshihikari × Inochinoichi as a nonrecurrent parent. Thorough the F2 and all BCnF2 generations, large, medium, and small grain segregated in a 1:2:1 ratio, indicating that the large grain is controlled by a single allele. Mapping by using simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Furthermore, the double dwarfness by combining d60 and d30 was obtained in F 3 via recombination breaking repulsion-phase linkage on rice chromosome 2 (Tomita and Tanaka 2019). d60 was also linked with a large grain gene GW2 on chromosome 2 (Tomita et al 2019). Next, the Koshihikari d60 line was crossed with a chromosome segment substitution line that carried a segment of chromosome 2 derived from Indica cultivar ‘Kasalath’ in the background of the japonica cultivar ‘Koshihikari’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the double dwarfness by combining d60 and d30 was obtained in F 3 via recombination breaking repulsion-phase linkage on rice chromosome 2 (Tomita and Tanaka 2019). d60 was also linked with a large grain gene GW2 on chromosome 2 (Tomita et al 2019). Next, the Koshihikari d60 line was crossed with a chromosome segment substitution line that carried a segment of chromosome 2 derived from Indica cultivar ‘Kasalath’ in the background of the japonica cultivar ‘Koshihikari’.…”
Section: Discussionmentioning
confidence: 99%
“…d60 confers a good semidwarf phenotype without detrimental effects on grain yield (Tomita & Ishimoto 2019). Furthermore, a semidwarf and large grain isogenic Koshihikari was developed by integrated with d60 and GW2 (Tomita et al 2019). Therefore, d60 is a useful gene source to diversify semidwarf rice varieties.…”
Section: Discussionmentioning
confidence: 99%
“…However, the genes that control its large grain size, approximately 1.5 times that of Koshihikari, have not been elucidated; hence, the production of "Inochinoichi" is limited to the area around Gifu Prefecture. In a previous study, we identified the gene GW2 responsible for the large grain size of Inochinoichi, an unused and buried genetic resource, and then applied the gene to develop a large-grain isogenic line of Koshihikari (Koshihikari GW2) [27]. Furthermore, in this study, we developed a large-grain/semidwarf isogenic line (Koshihikari sd1GW2) that incorporates both the large-grain gene GW2 and semidwarf gene sd1, which we believe is a large-grain rice cultivar with enhanced resistance to lodging.…”
Section: Discussionmentioning
confidence: 99%
“…It has since been clarified that sd1 is a deletion mutation of the GA20 oxidase gene in the gibberellin (GA) biosynthesis pathway (GA 20-oxidase, OsGA20ox2) [10][11][12] localized on A Japanese leading rice variety, Koshishikri, was used as a recurrent parent to develop isogenic lines based on Koshishikri. The Japanese rice variety Inochinoichi was used as a source of the large-grain gene GW2, which was identified in a previous study [27].…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than four genes linked to grain shape have been cloned in rice [ 7 , 8 , 9 ]. GW2 , the first major quantitative traits loci (QTL) isolated through map-based cloning, controls the width and weight of rice grains [ 10 ]. Similarly, the GS3 locus controls GL, TGW, GW, and grain plumpness [ 9 ], while GW8/OsSPL16 and GW7/OsSPL16 are determinants of GW and grain quality [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%